Plantar fasciitis: Current concepts to expedite healing - Glazer, J. L.; Brukner, P. (The Physician and Sportsmedicine, 2004)
Plantar fasciitis is a degenerative condition affecting many active people. Anatomic and biomechanical factors can contribute to its genesis, as can overuse. Clinicians can recommend correcting gait disorders, modifying footwear, using tension night splints, and stretching tight calf and plantar tissues to bring about lasting relief. Anti-inflammatory modalities, such as medications, iontophoresis, and corticosteroid injection generally provide temporary improvement. Recent studies on the efficacy of extracorporeal shock wave therapy are conflicting. A small percentage of patients who have refractory symptoms may benefit from surgical division of the plantar fascia.